ASSESSMENT OF THE INCREASE IN ECONOMIC POTENTIAL IN THE CLUSTERS OF THE TEXTILE INDUSTRY OF THE REPUBLIC OF UZBEKISTAN BASED ON AN INDUSTRY-SPECIFIC APPROACH - Rustamova Makhfuza Makhmudovna (American Journals, 2024)
This article is devoted to the study of the possibilities of increasing the economic potential in clusters of the textile industry using an industry-specific approach. The paper provides an overview of the textile industry, identifies its key characteristics and current challenges. Then a theoretical overview of the concept of clusters and their importance for the development of the industry is proposed. Based on these data, a methodology for assessing the economic potential of clusters is being developed, as well as an empirical analysis of the current state of clusters in the textile industry. As a result of the study, conclusions and recommendations are formulated aimed at improving the effectiveness of cluster initiatives in the textile industry and determining further research directions in this area.
Keywords: Clusters of the textile industry, economic potential, assessment, improvement, industry approach, competitiveness, innovation, sustainable growth, business development, technological base, production efficiency.